(untitled) (Journal of Information and Communication Technology, 2016)
A pedestrian evacuation under fire-spreading conditions is simulated by using a two-dimensional cellular automaton model. The proposed model presents a non-static fire-spreading behavior to avoid considerable discrepancies between reality and simulation. The proposed model adopts a circular fire front shape based on spiral fire movement. Moreover, four dynamic parameters are introduced to simplify the decision-making process of a pedestrian’s movement inside the layout during fire spreading. In addition, the proposed model includes the number of victims (i.e., caught in the fire) and the number of pedestrians who were evacuated safely. By analyzing these variables, a suitable evacuation plan enabling the control of crowd movements in different situations such as fire disasters can be consequently designed.